Postnatal Changes in Morphology and Morphometry of Testis of Guinea Fowl (Numida meleagris) - Tamilselvan, S; Mrigesh, Meena; Singh, Ishwar (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
This work was carried out on testes of 54 apparently healthy male guinea fowl (Pearl variety) at different age groups from Day old to 28 weeks at monthly interval. The testes were paired organs, located within the abdominal cavity attached to the dorsal body wall by mesorchium. After hatching at day old, the testes were indistinct and very difficult to demarcate. From 24 weeks onwards abundant fat tissues were observed in and around the testes and associated regions. They were small rice sized upto 8 weeks of age followed by elongated bean shaped, white to creamy white in colour from 12 to 28 weeks of age. The weight, length, width, and volume of guinea fowl testes increases as the age advanced.
Keywords: Guinea fowl; Morphology; Morphometry; Postnatal; Testis